2022
DOI: 10.1177/02654075211067441
|View full text |Cite
|
Sign up to set email alerts
|

Individual healing from infidelity and breakup for emerging adults: a grounded theory

Abstract: Objective: Infidelity is a relationship betrayal that can lead to significant negative individual and relational outcomes. When infidelity leads to relationship dissolution, this can further exacerbate these challenges. The purpose of the present study is to develop a grounded theory of the process of healing from infidelity and consequent relationship dissolution for non-straying partners who are emerging adults. Methods: We employed constructivist grounded theory (Charmaz, 2014) to conduct and analyze semi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Initial reactivity. There is consensus that in the aftermath of infidelity, partners experience intense pain, anger, a sense of betrayal, and loss of trust (Mitchell et al, 2021b;Fife et al, 2022;Olson et al, 2002). For many couples, there is uncertainty about whether to remain in the relationship and how to rebuild if they choose to do so (Butler et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Initial reactivity. There is consensus that in the aftermath of infidelity, partners experience intense pain, anger, a sense of betrayal, and loss of trust (Mitchell et al, 2021b;Fife et al, 2022;Olson et al, 2002). For many couples, there is uncertainty about whether to remain in the relationship and how to rebuild if they choose to do so (Butler et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Treatment often includes addressing contextual factors associated with infidelity (Fife et al, 2008; Snyder et al, 2004), such as a partner's reasons for engaging in infidelity. Even though there are studies on the treatment and healing for individuals and couples following infidelity (Fife et al, 2022, 2023; Gordon et al, 2004; Gossner et al, 2022; Mitchell et al, 2021), empirical research literature on infidelity itself is sparse, with little that is helpful for practicing clinicians (Blow & Hartnett, 2005a). Even less scholarship has focused on the thought processes or decision‐making of individuals who engage in infidelity.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Many experience infidelity as a significant relationship betrayal, resulting in mild to severe emotional, psychological, and relational distress. The impact depends on multiple factors, including the age of the participants, the nature of the commitment, and the length of the relationship (Allen & Atkins, 2012; Apostolou et al, 2019; Fife et al, 2022). Individuals whose partner has committed infidelity experience intense emotions such as betrayal, anger, self‐blame, and diminished feelings of self‐worth (Butler et al, 2022; Fife et al, 2022).…”
Section: Review Of Literaturementioning
confidence: 99%
“…A Portuguese study identified sexual infidelity rates of 68.7% for men and 66.7% for women in individuals who paid to register on the "Second Love" dating website (Rodrigues et al, 2017). Some studies identified the negative impact of infidelity on relationships and all those involved (e.g., Fife et al, 2022). Suspicion of infidelity can cause a partner to develop feelings of jealousy (Toplu-Demirtaş et al, 2022), and can lead to ambiguity in the relationship and intense emotions such as anger and sadness (Fife et al, 2022).…”
mentioning
confidence: 99%
“…Some studies identified the negative impact of infidelity on relationships and all those involved (e.g., Fife et al, 2022). Suspicion of infidelity can cause a partner to develop feelings of jealousy (Toplu-Demirtaş et al, 2022), and can lead to ambiguity in the relationship and intense emotions such as anger and sadness (Fife et al, 2022). Although there are many causes for the end of a marriage, such as family violence, low levels of partner trust, and low levels of love (Kloubučar & Simonič, 2017), infidelity is one of the most commonly reported causes of divorce (Apostolou et al, 2019).…”
mentioning
confidence: 99%